Anaerobic digestion of mixed dried fallen leaves by mixing with cow dung (Bangladesh Journal of Scientific and Industrial Research, 2015)
An investigation was carried out for the production of biogas from dry fallen leaves. The sample was collected from BCSIR campus of Dhaka in winter. The substrate was mixed leaves mainly mahogany (75%), eucalyptus (10 %) and rain tree (15 %) leaves. The study was carried out by whole leaves and crushed leaves directly followed by aerobic pretreatment at 8% total solid (TS) concentration. The raw materials were fed into two liter capacity glass bottle bio digester on batch basis for 60 days at ambient temperature. Different proportion of substrate and cow dung were mixed to get the optimum mix for maximum yield of biogas. The biogas reactor containing 6% crushed and pretreated leaves mixed with 2% cow dung (on 8% TS basis) gave maximum (0.199 l/g) biogas yield. The biogas yield from leaves without pretreatment was found to be too low (0.0106 l/g) for 8%. The COD reduction, VS reduction and methane composition of two biogas reactors have been determined where biogas yield were relatively higher. The maximum methane content of the biogas was found to be about 69.3%.Bangladesh J. Sci. Ind. Res. 50(3), 163-168, 2015